Men in love : a novel - Welsh, Irvine (Pegasus Books, 2026)
There wasn't an album they wouldn't buy, or a drug they wouldn't try. Then it spiralled out of control. They were left with nothing. Nothing but the eternal quest of all men - the search for love. Opening in the late 1980s as rave culture is born and moving into the 1990s, 'Men In Love' reunites the Trainspotting crew for a riotous new journey. Renton, Spud, Sick Boy and Begbie leave heroin behind and seek joy, and the hope of redemption, on the dance floor. Each wants to feel alive in the closing years of Thatcher's Britain, and they fill their days with sex and romance and trying to get ahead. Taking in Edinburgh, London, Amsterdam and Paris, the group charges towards an unexpected event - Sick Boy's wedding day. But is falling in love the answer, or just another doomed quest?